COVID-19 Disease and Viral Characteristics in a Long-Term Care Facility - Shauna Assadzandi; Emily Crocetti; Courtney S. Pilkerton; Amie M. Ashcraft; Carl D. Shrader (Marshall Journal of Medicine, 2021)
Due to the combination of age, comorbidities, and close living quarters, residents at long-term care facilities (LTCFs) are at particularly high risk of severe symptoms and death due to COVID-19. This cross-sectional study examines the relationship between demographic characteristics, symptom severity, and length of viral shedding in 49 residents testing positive for SARS-CoV-2 at a LTCF in West Virginia (WV). Over half of the residents were asymptomatic while nearly a quarter experienced severe symptoms. Women were more likely to be asymptomatic and age was not associated with symptom severity. While no specific medical condition was associated with symptom severity, having more chronic illnesses was associated. The length of time from initial positive to PCR negative ranged from 2 to 63 days with an average of 29 days. Given the variability in PCR testing reliability, 30 days of isolation and 2 consecutive negative PCR tests are recommended before reintegrating residents.